Β-Blocker treatment and prognosis in acute coronary syndrome associated with cocaine consumption: The RUTI-Cocaine Study. (1st June 2018) - Cediel, Germán; Carrillo, Xavier; García-García, Cosme; Rueda, Ferran; Oliveras, Teresa; Labata, Carlos; Serra, Jordi; Ferrer, Marc; de Diego, Oriol; Bayés-Genís, Antoni
Abstract: Background: The use of β-blocker therapy in the setting of acute coronary syndrome (ACS) associated with cocaine consumption (ACS-ACC) is discouraged due to the risk of coronary vasoconstriction. We examined the prognostic value of β-blocker therapy in a contemporary ACS cohort. Methods and results: Prospective, single-center study conducted between January 2001 and December 2014 that examined cocaine use among young (≤50-year-old) consecutive patients admitted with an ACS. During the study period, 1002 patients were admitted; of these, 57 (5.7%) had a positive cocaine urine test We collected data on clinical characteristics and major adverse cardiovascular events (MACE) during follow-up. Among ACS-ACC patients, 33 (57.9%) received β-blocker therapy during hospital admission and after discharge. During a median follow-up of 4.0 (IQR: 2.4–6.5) years after the index event, 2 (6.1%) patients treated with β-blocker therapy died and 6 (18.2%) experienced hospital re-admission for myocardial infarction (MI); in contrast, there were 5 (20.8%) deaths and 5 (20.8%) readmissions due to MI in patients without β-blocker therapy. Lower rates of MACE were observed in patients treated with β-blocker therapy (30.3%) than those without β-blocker therapy (41.7%). The 90-day survival was higher in patients treated with β-blocker therapy (87.5% vs. 100%; Log rank test p = 0.035). Conclusions: In patients with ACS-ACC, β-blocker treatment was associated with a significantly better clinical outcome, with lower rates of death and MI. Our findings support the evidence for long-term β-blocker administration in high-risk patients and highlight the need for large prospective multicenter studies of β-blocker treatment in ACS-ACC. Highlights: The use of β-blockers in ACS-ACC is discouraged due to the risk of coronary vasoconstriction. In patients with ACS-ACC, β-blocker is associated with a better clinical outcome. Myocardial protective benefits of β-blockers may offset cocaine-derived concerns.